2020
DOI: 10.1080/13575279.2020.1765149
|View full text |Cite
|
Sign up to set email alerts
|

“Do I Read it? No”. Knowledge Utilisation in Child Welfare Decisions

Abstract: Much as one would like to be able to base permanency decisions on the solid ground of empirical findings and objective knowledge, the nature of child abuse precludes this possibility. In the absence of any unitary knowledge base, it is important to know what knowledge social workers use to inform their permanency decisions. This article presents findings from an exploratory indepth qualitative research project with the objective of exploring the knowledge that social workers use to make decisions regarding per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 80 publications
0
2
0
3
Order By: Relevance
“…However, there was a sense that the participants were relying on their practice wisdom and knowledge that they had built up over time, rather than applying evidence-informed practice or using a safeguarding assessment methodology. In terms of the assessment of threshold information required in adult safeguarding, it would appear that practitioners are relying on their intuition (McCafferty, 2022; McCafferty and Taylor, 2022). Studies have shown that the application of knowledge diminishes over time after undertaking a period of training (Pike et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, there was a sense that the participants were relying on their practice wisdom and knowledge that they had built up over time, rather than applying evidence-informed practice or using a safeguarding assessment methodology. In terms of the assessment of threshold information required in adult safeguarding, it would appear that practitioners are relying on their intuition (McCafferty, 2022; McCafferty and Taylor, 2022). Studies have shown that the application of knowledge diminishes over time after undertaking a period of training (Pike et al , 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Vetenskapligt kunskapsutnyttjande innefattar två komponenter, vetenskaplig kunskap samt kunskapsutnyttjande. Med vetenskaplig kunskap avses forskningsresultat som har framkommit utifrån vetenskapligt etablerade och vedertagna metoder (McCafferty, 2022). Vi utgår från följande definition av begreppet kunskapsutnyttjande i vår artikel: Kunskapsutnyttjande definieras som en process där en professionell tar del av och bedömer kunskap (t.ex.…”
Section: Studiens Fokusunclassified
“…Forskning från Nordirland som inkluderade socialarbetare verksamma inom individoch familjeomsorg fann att de primärt förlitade sig på lagstiftning, policy och praxis i sina beslut. Vidare använde de sig av sin arbetslivserfarenhet, medan användandet av forskning eller teori konstaterades vara mycket lågt (McCafferty, 2022;McCafferty & Taylor, 2022). McCafferty och Taylor (2022) fann att socialarbetarna stötte på flera hinder: tilltron till den egna förmågan att använda teori och forskning samt organisatoriska förhållanden, exempelvis tidsbrist.…”
Section: Tidigare Forskningunclassified
See 1 more Smart Citation
“…These technological capacities, such as improvement in search platforms and facilities, need to be used wisely and efficiently. The skills of identifying relevant research and developing empirically-based understanding and explanations are yet to be tightly woven into the fabric of everyday social work practice and decision making (McCafferty, 2020;McCafferty and Taylor, 2020;.…”
Section: Introductionmentioning
confidence: 99%